Comparison of topical purslane & topical 0.1% triamcinolone acetonide in the management of oral lichen planus - a double blinded clinical trial - Murugan, Arul Jothi; Ganesan, Anuradha; Aniyan, Yesoda K.; Lakshmi, Krithika Chandrasekar; Asokan, Kannan (BMC oral health, 2023)
Aim and background Oral lichen planus (OLP) is a chronic autoimmune mucocutaneous disorder of unknown etiology and treatment is targeted at alleviating symptoms. At present, corticosteroids are the mainstay treatment, and their side effects hamper their long-term use, demanding alternative therapy. This study intended to assess the efficacy of topical purslane (Portulaca oleracea) at two concentrations, 5% and 10%, in OLP and to compare the level of clinical improvement in comparison to topical 0.1% triamcinolone acetonide gel. Materials and methods After sample size determination, thirty-four subjects confirmed histopathologically with OLP were included in the study. They were divided into 3 groups, Group 1(Control) was treated with 0.1% triamcinolone acetonide, and Group 2(Case) and 3 (Case) were treated with topical purslane 5% and 10%, respectively. They were examined at baseline, 14 days, 30 days, 60 days, and 90 days. Clinical improvement was then analyzed at the end of 90 days using a visual analog scale (VAS) and Thongprasom's criteria. Results The study was analyzed statistically and a P value of < 0.05 was considered statistically significant. Intragroup comparison revealed a statistically significant difference between the five time periods (baseline, 14 days, 30 days, 60 days, and 90 days) for the study variables (burning sensation, pain, lesion score, clinical response, symptomatic response) for all three groups (p = 0.001). Alleviation of all symptoms and remission of the lesion were noted for all three groups at the end of three months. Conclusion Purslane is a magical herb with a plethora of rich nutrients, ease in accessibility and devoid of side effects. It was concluded that its preparation is beneficial and can be a safer alternative long-term drug for the management of OLP. Clinical significance With available literature evidence, our present study is the first of its kind to formulate a topical gel with purslane to treat symptomatic OLP. Our study had a longer follow-up of 3 months compared to other studies in the literature. Keywords: Antioxidant, Clinical improvement, Oral lichen planus, Steroids, Topical purslane